IMPLEMENTASI PENGGUNAAN APLIKASI ZOOM DALAM PEMBELAJARAN TEMATIK KELAS V SD ISLAM AL-AZHAR 21 PONTIANAK - Ega Diana Sari; Hery Kresnadi; Rio Pranata (Universitas Tanjungpura, 2022)
AbstractThis study aims to describe the preparation, implementation, and barriers to implementing the zoom meeting application in class V thematic learning at Al-Azhar 21 Islamic Elementary School Pontianak. The research method used is qualitative research. The data sources of this research are documentation related to thematic learning through zoom meetings, observation results from the documentation and the results of interviews with teachers. Data collection technique This research is documentation, interviews and observations. Research result shows that the preparations made have been good because they meet the components preparation of learning through a zoom meeting, namely the Implementation Plan Learning, preparing learning materials, preparing methods learning that will be used, determine the type of learning media, and set up a meeting link. Likewise with the implementation of learning through the zoom meeting this went well because it was appropriate between RPP and implementation. Barriers to learning through zoom meeting, which is an unstable network, student discipline in learning, as well as the resilience of students when learning.Keywords: Implementation, Thematic Learning, , Zoom Meeting.